Simulink Based Multi Variable Solar Panel Modeling - Chandani Sharma; Anamika Jain (Institute of Advanced Engineering and Science, 2014)
Solar Energy, the most abundant and widely used Renewable Energy is not only reliable, scalable but serves solution to global warming around the world. This energy is used for electricity generation using Photovoltaics (PV) converting Solar Energy into electricity. Photovoltaics (PV) play significant role for future Distributed and Renewable Energy Generation Systems (DG). This study is an effort to visualize simulation tool for solar cell array under rapidly changing solar radiation and temperature by inserting a test signal in the control input. The main objective is to find the parameters of the nonlinear I-V and P-V equation by locating the curve at three points: short circuit current, open circuit voltage and maximum power. Future Smart Grids can be optimized if computerized and designed using mathematical modeling and simulation system at STC. Case study relative to factors including weather and seasonal variations is tested through SIMULINK model. Predicted changes are configured for determination of MPP. The proposed model is based on variations by changing absorption of light with physical inspections for data corresponding to low and high temperatures. DOI: http://dx.doi.org/10.11591/telkomnika.v12i8.6071